Pakistan : Can Low-Cost Private Schools Improve Learning? - World Bank (Washington, DC, 2014)
Education is central to giving children the building blocks for a life free of poverty. When schools fail to deliver quality education, children are left without the skills and knowledge they need to realize their capabilities and become productive adults. This isn't just a problem of insufficient supplies or poor facilities. Policymakers and education experts in developing countries often grapple with the problems of accountability: it can be hard to create mechanisms for holding schools responsible for student achievement, but across the world, promising innovations are being introduced. The World Bank is working hard to help countries meet the United Nations Millennium Goal of universal primary education, and to ensure that schools teach effectively and students can learn. To understand whether low-cost private schools can improve access to education and promote student learning especially in cases where public schools aren't succeeding the World Bank carried out an evaluation of a new public-private education partnership in Pakistan at the request of the government. Private schools in the program receive a per-student monthly subsidy in exchange for waiving tuition for all students and meeting a minimum pass rate in a standardized academic test administered to students.